Sustainable nutrient substrates for enhanced seedling development in hydroponics - Zhao, Zhitong (2023)
Sustainable agriculture can be achieved by upcycling and repurposing organic wastes for high-value applications. Keratin and cellulose are two natural biopolymers which are plentiful in biowastes such as hair, poultry feathers, wood shavings, and vegetable trimmings. In this study, these waste-derived biopolymers are converted into bioactive nutrient substrates that can support crop development in hydroponic culture systems. Keratin extracted from human hair (HHK) and cellulose nanofibers (CNFs) obtained from wood pulp were fabricated into composite substrates by freeze-drying. The substrates exhibited highly microporous structures, superior hydrophilicity, and excellent mechanical resilience. The obtained substrates not only serve as a physical carrier to support seed germination and seedling development but also function as advanced nutrient delivery platforms by the incorporation and controlled release of micronutrient-doped carbon dots, in addition to keratin degradation. Functional experiments using the model plant Arabidopsis and crops including Bok Choy (Brassica rapa) and Arugula (Eruca vesicaria) indicated that these substrates have the potential to be customized for enhanced seedling development in comparison to conventional substrates. This study demonstrates the feasibility and potential of upcycling and repurposing keratinous and cellulosic wastes to provide a sustainable solution for targeted nutrient delivery to crops.